New frontiers in the platform economy: place, sociality, and the embeddedness of platform mobilities. Issue 5 (3rd September 2022) - Gibbings, Sheri Lynn; Frey, Bronwyn; Barker, Joshua
Abstract: The aim of this special issue is to bring together ethnographic scholarship on last-mile logistics work, sometimes called 'platform labour', into a more direct conversation with the mobilities framework. The introduction argues that although platform mobilities often employ a rhetoric of unrestricted flow across time and space, the movements of people and technologies associated with them are in fact entangled in the social, political, economic, and ethical relationships that characterise the places in which they operate, and in unexpected ways. The contributions, based in a wide range of settings globally, provide empirical insights into how platform mobilities are embedded in a range of both new and long-standing societal dynamics that cannot be described through relations of economic extraction alone.